Characteristics of Parvovirus B19 infection presentation in adults versus children - Prof Natalia Pshenichnaya; Regina Ionova; PhD Irina Lizinfeld (International Journal of Infectious Diseases)
Introduction: Parvovirus B19 infection, primarily diagnosed in children, has emerged as a relatively new disease in adults. In recent years, its incidence has risen among adults, presenting with various clinical manifestations. Methods: Clinical features of parvovirus infection in adults (n = 69) and children (n = 49) treated in infectious diseases hospitals in Moscow were analyzed. The average age of children was 8 years old (Q1–Q3: 6–11), and that of adults was 33 years old (Q1–Q3: 28–40). The diagnosis was confirmed by PCR (parvovirus B19 DNA detection). Results: Among children, females were 36.7%, and among adults, 63.8% (p = 0.004). The average hospitalization duration was 5 days [Q1–Q3: 4–7] for adults and 4 days [Q1–Q3: 3–5] for children (p < 0.001). Increased body temperature was recorded in 80% of adults and 90% of children. Conjunctivitis was present in 81.6% of children and 18.8% of adults (p < 0.001), and nasal congestion was present in 81.6% of children and 20.3% of adults (p < 0.001).Skin rash was absent in 6.1% of children and 17.4% of adults. Maculopapular rash occurred in 57.1% of children and 66.7% of adults, while hemorrhagic rash occurred in 8.2% and 15.9%, respectively. Spot and petechial rashes were observed only in children at 24.5% and 4.1%, respectively (p < 0.001). Trunk rash was observed in 67.3% of children and 47.8% of adults, while lower extremity rash affected 69.4% of children and 65.2% of adults. Upper extremity rash was typical for 75.5% of children and 45.6% of adults. Facial rash was present in 42.9% of children and 35.3% of adults. Palm rash was observed in 14.3% of children and 26.1% of adults; rash on low extremities was observed in 14.3% of children and 14.5% of adults. Genital rash was absent in all children but observed in 7.2% of adults.Slapped cheek rash was present in 36.7% of children but absent in adults (p < 0.001).Thrombocytopenia was observed in 10.2% of children and 42.0% of adults (p < 0.001). Elevated CRP levels were seen in 83% of adults [Q1–QQ3: 8.00; -62.90] and 41.1% of children [Q1–QQ3: 2.00–9.30].Bacterial complications occurred in 43.5% of adults and 14.3% of children. Discussion: In adults, the disease is more severe compared to children. Significant differences in clinical manifestations of parvovirus infection between children and adults emphasize the need for an individualized approach to diagnosis and treatment. Conclusions: Following the COVID-19 pandemic, parvovirus infection is increasingly being recognized in both adults and children, presenting with diverse clinical manifestations. These differences should be considered in differential diagnosis with diseases sharing similar clinical symptoms. Physicians should account for age differences when diagnosing and treating the condition.